2022
DOI: 10.1021/acsomega.2c02260
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Oncogenic LncRNA DANCR with Targeted ECO/siRNA Nanoparticles for Non-Small Cell Lung Cancer Therapy

Abstract: Long noncoding RNA (lncRNA) differentiation antagonizing noncoding RNA (DANCR) is a proven oncogenic lncRNA across multiple cancer types. Its effects on cancer cell migration and invasion position it as a potential target for therapy on multiple levels of gene regulation. DANCR is overexpressed in non-small cell lung cancer (NSCLC), the most common lung cancer subtype with poor patient survival. To effectively deliver small interfering RNA (siRNA) against DANCR for NSCLC therapy, we used arginine-glycine-aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…ECO with an ethylenediamine head group, two cysteine-based linker groups, and two oleoyl tails has been extensively explored for in vivo delivery of nucleic acids for various applications, including siRNA gene regulation for cancer therapy, CRISPR/Cas9 for gene editing, and gene replacement therapy with plasmid DNA for eye genetic disorders [ 88 – 101 ]. ECO readily self-assembles with nucleic acids of any sizes to form stable LNPs without helper lipids.…”
Section: The Evolution Of Lnp For Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…ECO with an ethylenediamine head group, two cysteine-based linker groups, and two oleoyl tails has been extensively explored for in vivo delivery of nucleic acids for various applications, including siRNA gene regulation for cancer therapy, CRISPR/Cas9 for gene editing, and gene replacement therapy with plasmid DNA for eye genetic disorders [ 88 – 101 ]. ECO readily self-assembles with nucleic acids of any sizes to form stable LNPs without helper lipids.…”
Section: The Evolution Of Lnp For Gene Deliverymentioning
confidence: 99%
“…RGD peptide with a PEG spacer was used to modify siRNA ECO LNP for targeted delivery in cancer via systemic injection, which has demonstrated excellent in vivo efficacy in mouse tumor models [ 91 , 96 , 97 , 101 ]. Retinoid analogues with a PEG spacer were also used to target the retinal pigmented epithelium for retinal gene therapy using ECO plasmid LNP [ 94 , 99 ].…”
Section: The Evolution Of Lnp For Gene Deliverymentioning
confidence: 99%
“…This knockdown of DANCR, especially within Epidermal growth factor receptor (EGFR)-inhibitor-resistant NSCLC, exhibited reduced cell migration and invasion. [157]…”
Section: Lung Cancermentioning
confidence: 99%
“…(E) Blocking by excess free RGD peptide reduces the uptake of RGD-targeted nanoparticles relative to the unblocked group. Reprinted from ref [157] under the terms of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/). The CGE/FAM-si-TMEM44-AS1 showed higher concentrations in organs such as the kidneys, lungs, heart, liver, and spleen compared to FAMsi-TMEM44-AS1.…”
Section: Gastric Cancermentioning
confidence: 99%
“…The development of siRNAs and antisense oligonucleotides (ASOs) have the same effect on degrading the lncRNAs, having pointed out another direction to knock down the expression of lncRNAs (Chen et al, 2021b). For instance, The researchers found that the expression of lncRNA DANCR could be modulated with siRNA nanoparticles for the treatment of non-small cell lung cancer (Nicolescu et al, 2022). Other researchers have constructed an ASO targeting lncRNA MALAT1, which can significantly inhibit the metastasis and invasion of rat lung cancer cells.…”
Section: The Rna Interfering Drugs Of H19mentioning
confidence: 99%